The self-fulfilling prophecy of adolescent social expectations. (November 2016) - Loeb, Emily; Hessel, Elenda T.; Allen, Joseph
Adolescents' negative social expectations of their peers were examined as long-term predictors of problematic self-reported social functioning. Early adolescent negative expectations were hypothesized to predict risk-averse functioning in late adolescence that would ultimately contribute to confirmation of those expectations. Utilizing observational data and friend- and self-reports from a community sample of 184 adolescents followed from ages 13 to 25, adolescents with more negative expectations were found to have become increasingly submissive with friends over time and were rated as less romantically appealing by late adolescence (after controlling for baseline levels of these variables, baseline friend-rated social competence and self-reported depressive symptoms). In turn, submissiveness and romantic appeal predicted problematic self-reported social functioning well into adulthood and mediated the relationship between adolescent negative expectations and problematic self-reported adult social functioning. These findings support the possibility of a self-fulfilling social process unfolding from early adolescence to adulthood.